2017
DOI: 10.1111/tpj.13743
|View full text |Cite
|
Sign up to set email alerts
|

Multiple marker abundance profiling: combining selected reaction monitoring and data‐dependent acquisition for rapid estimation of organelle abundance in subcellular samples

Abstract: SummaryMeasuring changes in protein or organelle abundance in the cell is an essential, but challenging aspect of cell biology. Frequently‐used methods for determining organelle abundance typically rely on detection of a very few marker proteins, so are unsatisfactory. In silico estimates of protein abundances from publicly available protein spectra can provide useful standard abundance values but contain only data from tissue proteomes, and are not coupled to organelle localization data. A new protein abundan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…This is mostly because the fractionation of mitochondria from Arabidopsis seeds is practically impossible and thus the identification and quantitation of mitochondrial proteins must rely on the use of the whole seed protein extract. With the rapid advancement of mass spectrometry techniques, the application of targeted proteomics for the detection and quantitation of mitochondrial proteins in complex samples obtained from plant material has become a promising analytical tool in such studies (Hooper et al, 2017 ). In this work, we presented MRM as a sensitive and specific technique for estimating mitochondrial protein abundances in dry and germinating Arabidopsis seeds without the organelle enrichment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is mostly because the fractionation of mitochondria from Arabidopsis seeds is practically impossible and thus the identification and quantitation of mitochondrial proteins must rely on the use of the whole seed protein extract. With the rapid advancement of mass spectrometry techniques, the application of targeted proteomics for the detection and quantitation of mitochondrial proteins in complex samples obtained from plant material has become a promising analytical tool in such studies (Hooper et al, 2017 ). In this work, we presented MRM as a sensitive and specific technique for estimating mitochondrial protein abundances in dry and germinating Arabidopsis seeds without the organelle enrichment.…”
Section: Discussionmentioning
confidence: 99%
“…The recent development of a mass spectrometry-based targeted proteomics approach, such as Multiple Reaction Monitoring (MRM: the acquisition of multiple product ions from one precursor ion by Selected Reaction Monitoring (SRM) transitions), and its utilization for the quantitative analysis of peptides derived from proteins of specific organelles in plant cells has become a powerful, hypothesis-driven analytical tool to achieve specific, sensitive, and precise protein quantification (Zulak et al, 2009 ; Hall et al, 2011 ; Fan et al, 2012 ; Hooper et al, 2017 ). The high specificity of MRM analysis comes from the mass measurement (accurately measured to an atomic mass unit) of the whole peptide and its multiple fragments, the unique peptide ion fragmentation pattern, and the precise peptide retention time in the liquid chromatography (LC) separation (Liebler and Zimmerman, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…LOPIT resulted in the identification of 345 ER-, 46 TGN-, and 397 Golgi-resident proteins in three spatially distinct clusters, along with comprehensive lists of resident protein markers for all other organelles (Supplemental Figure 1; Supplemental Data Set 1). The currently annotated Arabidopsis Golgi proteome (covering all cell types) is estimated at ;530 proteins (Hooper et al, 2017b), suggesting that we identified a large majority of resident Golgi proteins present in our cell line.…”
Section: Establishing Updated Subproteomes For the Golgi And Other Ormentioning
confidence: 91%
“…To find targeted processes or protein hotspots sensitive to Ssulfenylation, we first determined the subcellular distribution of the identified S-sulfenylated proteins ( Fig. 2A and Dataset S1) (28,29). The best-represented subcellular compartments are cytoplasm (48%), chloroplast (18%), mitochondrion (13%), and nucleus (12%).…”
Section: Bioinformatics Analysis On the Target Specificity Of S-sulfementioning
confidence: 99%